Oral Mass of a Fetus Incidentally Found during Second Trimester: Ultrasound Survey and Postnatal Prognosis of the Baby - Huseyin Durukan; Savas Gundogan; Murside Çevikoğlu Kıllı; Talat Umut Kutlu Dilek (Hindawi Limited, 2018)
Ultrasound (USG) and magnetic resonance imaging (MRI) can be used to detect and evaluate the face and neck tumors during the in-utero period. We reported and discussed an oral mass which was diagnosed incidentally at mid-trimester exam and managed successfully.